The Effect of Social Support on Self Efficacy in Job Search to Improve Career Adaptability - Fredy Susanto; Ina Syarifah; Bias Nur Elmira (Jurnal Multidisiplin Madani, 2024)
Career decision-making is an important stage for students, specifically the process of making career decisions that is realized through the selection of companies and job positions. To make an optimal selection, many aspects are involved or influence the decision, both internal and external factors. Career decision-making should also align with the abilities possessed by the students themselves. One of the factors that can influence the decisiveness of students' career decisions from the individual perspective is Self-Efficacy, while from the environmental perspective, one of the factors is Social Support. The purpose of this research is to determine the extent to which social support and self-efficacy in job search influence the development of Career Adaptability in final-year students. This research uses a quantitative approach with a population consisting of all university students in the city of Madiun. The sample was taken using purposive sampling based on the population criteria. Data analysis was conducted using multiple regression with SPSS software